Los juegos tradicionales en el desarrollo de la Expresión Corporal en los niños del Centro de Educación Inicial “Margarita Santillán de Villacís”, de la parroquia San Luis, cantón Riobamba, Provincia de Chimborazo, año lectivo 2013-2014 - Ayala Santillán, Juanita Emilia (2016)
This research was conducted in the Initial Educational Center”Margarita Santillan de Villacis”,located in the parish of San Luis in the canton Riobamba in the province of Chimborazo;the subject being investigated is “Los juegos Tradicionales en el desarrollo de la Expresion Corporal (Traditional games in the development of corporal expression) in children in the Center of Initial Education Margarita Santillan de Villacis, of the San Luis parish, canton Riobamba, Chimborazo province.” In Chapter I, the problems in the institution were identified, which allowed us to formulate the problem and set targets at the same time we could justify and give due importance to this research. In Chapter II, it is evident that similar but different proposed research, so it is a cause of concern to teachers at is level of education, the necessary literature to serve as a theoretical basis was consulted, the in Chapter III are the methods, type and design of this research, like the people with whom he worked, to which are tabulated, graphed, analyzed and interpreted in chapter IV, the same that serve to raise the relevant conclusions and recommendations are found in chapter V, where it is determined the urgent need to incorporate traditional games as an active technique to develop body expression in children, giving the teacher the possibility of applying innovative activities inside and outside the classroom.